Penilaian Kerentanan dan Potensi Kerusakan Bangunan Akibat Tsunami di Desa Pejamben, Pandeglang, Banten - Meassa Monikha Sari; Aulia Kusumawati (Jurnal Serambi Engineering, 2023)
The study of tsunami disaster in Banten is less even though Banten is very susceptible to the earthquakes, and the Anak Krakatau Volcano is still exist as a tsunami trigger. The building vulnerability and capacity assessments are important to reduce the risk of casualties and substantial damages of tsunami. This study aims to assess the level of vulnerability of buildings, analyze the potential risk of building damage and get community capacity in dealing with tsunami. Data collection was carried out by surveying to the field to obtain the coordinates and types of buildings, coastal defense conditions and inundation heights. The distribution of questionnaires and interviews was also carried out to determine the community capacity. The data processing is using excel, utmgeomap, arcmap and spss. The results of the study  are concluded that out of a total of 647 in Pejamben Village has varying levels of vulnerability, namely moderate vulnerability (500units), high (142units) and very high (5units). The highest potential risk of building damage is moderate damage (75%) of the total building, heavy damage is 22%, light damage is about 5% and total collapse is 1%. The community capacity shows in the good category with a knowledge index of 77%.